Nutritional evaluation and transcriptome analyses of short-time germinated seeds in soybean (Glycine max L. Merri.) - Wei Hu (Nature Portfolio, 2021)
Abstract Germination is a common practice for nutrition improvement in many crops. In soybean, the nutrient value and genome-wide gene expression pattern of whole seeds germinated for short-time has not been fully investigated. In this study, protein content (PC), water soluble protein content (WSPC), isoflavone compositions were evaluated at 0 and 36 h after germination (HAG), respectively. The results showed that at 36HAG, PC was slightly decreased (P > 0.05) in ZD41, J58 and JHD, WSPC and free isoflavone (aglycones: daidzein, genistein, and glycitein) were significantly increased (P < 0.05), while total isoflavone content was unchanged. Transcriptomic analysis identified 5240, 6840 and 15,766 DEGs in different time point comparisons, respectively. GO and KEGG analysis showed that photosynthesis process was significantly activated from 18HAG, and alternative splicing might play an important role during germination in a complex manner. Response to hydrogen peroxide (H2O2) was found to be down regulated significantly from 18 to 36HAG, suggesting that H2O2 might play an important role in germination. Expression pattern analysis showed the synthesis of storage proteins was slowing down, while the genes coding for protein degradation (peptidase and protease) were up regulated as time went by during germination. For genes involved in isoflavone metabolism pathway, UGT (7-O-glucosyltransferase) coding genes were significantly up regulated (40 up-DEGs vs 27 down-DEGs), while MAT (7-O-glucoside-6′′-O-malonyltransferase) coding genes were down regulated, which might explain the increase of aglycones after germination. This study provided a universal transcriptomic atlas for whole soybean seeds germination in terms of nutrition and gene regulation mechanism.